Re-fashioning Best Practices in the Filing Systems of Public Sector Organisations - Tuladhar, Subarna Man (Administration and Management Review, 2009)
Filing is the method of storage and retrieval of information. The author in this article not only mentions several file classification systems and their requirements but also explains how all the files of different sections within an organization can be housed in one place centrally or in different places separately and independently in their most useful paper or electronic forms. User requirements are the prime considerations in selecting the type of filing registry in an organization and the author seems to recommend a combination of both kinds of filing registries for the government ministries and departments. Administration and Management Review Vol. 20, No. 1, January, 2008, Page 33-44